Isolation, characterisation and identification of cellulolytic bacteria from rice straw - Teo, Seng Chong, 1993- , author 612670; Chong, Chun Shiong, supervisor 421074; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Biologi Industri)) - Universiti Teknologi Malaysia, 2017